KEKUATAN PEMBANGUNAN EKONOMI MENGUBAH MAKNA EKONOMI KOMPARATIF MENJADI KEKUATAN EKONOMI KOMPETITIF - Cindy Aprilia (Asosiasi Dosen Muda Indonesia, 2023)
Economic development aims to increase people's purchasing power by increasing their standard of living with employment opportunities that can be supplemented by local jobs, especially jobs that have a national impact on the economy, for other activities, and are expected to improve people's lives. Economic thought was born from the abolition of goods which, according to its founders, were deemed useless - ceteris paribus. The concept of competitive advantage is not the same as the concept of profit, the concept of profit is not the same as the concept of absolute value, and profit is a combination of the three. By definition, the concepts of comparative advantage and competitive advantage have different meanings. The analytical approaches used to measure value and create value from the two perspectives are also different. Achieving and maintaining an advantage over relationships and competition is the key to long-term corporate success, therefore, understanding corporate assets and behaviors that can lead to synergies and competitive advantage is an important issue in leadership research.